Implementación de indicadores de gestión en la operación marítima de contenedores en el puerto de Santa Marta (2021)
The city of Santa Marta has grown around its port that has placed it in the same development path as these important world capitals. However, the port of Santa Marta has become a fundamental stage for their growth. Considering the increasing development and economic growth that comes day after day presenting business activity in the world we live in, in which they are very the terms globalization and / or globalization are common, it is worth highlighting the role essential that logistics and all its components perform in the appropriate international trade gear And it is that the panorama that is glimpsed in the world in which it is characterized today, reflects a tough battle, in which only organizations that manage to be competitive; every day the different companies must concentrate on rethinking one and its processes again, in order to improve its productivity indicators, putting a view in their procedures and their results, and another in what they are doing their competitors. Undoubtedly, those who achieve success in the business environment are identified by the effectiveness of its logistics processes, optimizing to the maximum the resources with which account, by aligning their operations, allowing them to generate high quality standards and time savings, which every day is more equivalent to money costs; What is surprising is that it is not enough to achieve the proposed objectives to today, since tomorrow the competitors will have surpassed the results obtained.